Accurate photon echo timing by optical freezing of exciton dephasing and rephasing in quantum dots - Alexander N. Kosarev (Nature Portfolio, 2020)
Ultrafast optical manipulation of excitons in semiconductor nanostructures offers practical access to quantum phenomena in condensed matter. The authors demonstrate a new scheme to control the exciton dephasing in large ensembles of quantum dots by application of resonant optical pulses that enable promising routes in the quest for quantum memories for information and communication technologies.